A system design for distributed energy generation in low temperature district heating (LTDH) networks - Jones, Sean; Gillott, Mark C.; Boukhanouf, Rabah; Walker, Gavin S.; Tunzi, Michele; Tetlow, David; Rodrigues, Lucélia Taranto; Sumner, M. (2017)
Project SCENIC (Smart Controlled Energy Networks Integrated in Communities) involves connecting properties at the University of Nottingham’s Creative Energy Homes test site in a community scale, integrated heat and power network. Controls will be developed to allow for the most effective heat load allocation and power distribution scenarios. Furthermore, the system will develop the prosumer concept, where consumers are both buyers and sellers of energy in both heat and power systems.